Peri-Selective Direct Acylmethylation and Amidation of Naphthalene Derivatives Using Iridium and Rhodium Catalysts - Kona, Chandrababu Naidu; Oku, Rikuto; Nishii, Yuji; Miura, Masahiro (Synthesis, 2021)
An iridium-catalyzed acylmethylation and a rhodium-catalyzed amidation of naphthalene derivatives are reported, adopting sulfoxonium ylides and dioxazolones as carbene and nitrene transfer agents, respectively. The use of SMe group as a directing group was key to ensure the peri-selective functionalization, and it can be easily removed or diversely transformed to other synthetically useful functionalities after the catalysis.
Keywords: C–H Activation; iridium; rhodium; alkylation; amidation